Age and job-specific skill obsolescence: the moderating effects of human resource practices. Issue 4 (21st December 2020) - Yue, Lin-Yang; Huang, Wei-de
Abstract : Purpose: This paper aims to examine the J -shaped relationship between age and job-specific skill obsolescence (JSSO), and the differential moderating effects of development and maintenance HR practices on this relationship. Design/methodology/approach: Regression models of survey data obtained from a sample of 722 Chinese knowledge workers were used to test the hypotheses. Findings: The results show that among women age and JSSO are J -shaped related and the relationship weakens under high development HR practices; while among men the J -shaped age-JSSO relation is significant only under low maintenance HR practices. Research limitations/implications: This research is subject to the cross-sectional design, and the sample is restricted to knowledge workers. Originality/value: This study advances previous studies that hold a linear (positive or negative) age-JSSO relationship by theorizing and testing a J -shaped one. The differentiated moderating effects of two bundles of HR practices proved improves our knowledge about how to use HR practices appropriately to sustain employee work competency in the context of workforce aging.